Role of alpha-fetoprotein in complex diagnostics of progressing course of chronic hepatitis B and C - I. A. Belavina; O. P. Dudanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine the role of alpha-fetoprotein (AFP) in complex diagnostics of progressing course of chronic hepatitises B and C. Material and methods. Overall 69 patients with chronic viral hepatitis were investigated: 39 with chronic hepatitis B (CHB) and 30 — with chronic hepatitis C (CHC) without signs of cirrhotic transformation and liver cancer. The diagnosis was verified by clinical, laboratory and morphological – with assessment of histological activity index (HAI) and histological sclerosis index (HSI), instrumental (transabdominal ultrasound, Doppler ultrasonography of portal blood flow), virologic studies. AFP level was determined by chemiluminescent solid-phase analysis by «Immulite AFP» test-systems (USA). Results. The mean level of AFP CHB patients 2,6 times, and in CHC patients – 5,4 times exceeded score in the control group. The level of AFP closely correlated with necroinflammatory parameters, sclerosis and portal blood flow, especially in hepatitis of high activity (HA). At HA CHB relation of AFP to histological activity (0,93; p<0,01), sclerosis index (0,69; p <0,01), hepatic vascular index (–0,93; p<0,01) was maximal. At HA CHC close correlations were revealed between AFP and ALT (0,56; p<0,05), histological activity (0,73; p<0,01), HSI (0,65; p<0,05) and portal hypertension index (0,45; p<0,01)Conclusions. AFP can be used for diagnostics necroinflammation progression, sclerosis and impairment of perfusion of the liver in patients with chronic viral hepatites B and C.